Boosting the synthesis of 3-acetamido-5-acetylfuran from N-acetyl-D-glucosamine: understanding the significant role of homogeneous Cl - - Delong Yang; Jinhang Dai; Ziting Du; Qingya Cao; Gang Chen; Ting Qi; Weilu Wang; Fukun Li (Carbon Neutrality)
Abstract Since 3-acetylamino-5-acetylfuran (3A5AF) has been regarded as a promising nitrogen-containing synthon, the conversion of renewable chitin and its monomer N-acetyl-D-glucosamine (NAG) to 3A5AF is of significance. In this paper, we compared the catalytic activity of several Cl-containing compounds and found that LiCl exhibited superior performance. The effects of solvent, catalyst dosage, reaction temperature, and reaction time on the synthesis of 3A5AF were investigated. Under the optimized conditions, about 60% yields of 3A5AF were obtained in N-methyl-2-pyrrolidone (NMP) or dimethylacetamide (DMA) medium. The spent LiCl and DMA could be recycled and reused, without obvious decrease of 3A5AF yield. Moreover, the formed 3A5AF could be purified by a facile procedure. Experiment results and density functional theory (DFT) calculations revealed that homogeneous Cl− was vital for 3A5AF formation. This study provides an example for the effective conversion of chitin biomass to value-added compounds.